Pendekatan problem solving untuk meningkatkan kemampuan berfikir kritis matematis siswa kelas VIII - Padmiati, Annisa Dwi; Sariningsih, Ratna; Rohaeti, Euis Eti (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2024)
This research aims to analyze the increase in students' critical mathematical thinking skills after being given treatment using the approach problem solving. This research was carried out at SMP Negeri 36 Bandung in class VIII with a sample size of 25 students. The method used in this research is quasi-experimental. The instrument and learning tools used are questions pretest and questions posttest. The data collection technique in this research is 5 descriptive questions with indicators of critical thinking abilities. Data analysis was carried out using the N-Gain test, normality test, test Mann-Whitney, homogeneity test, and Test independent t-test. The results of the research showed that there was an increase in students' mathematical critical thinking abilities by learning using problem solving approach.